Refleksi Kurikulum Bahasa Arab Daring di MI Al-Islamiyah Karanganyar, Paiton - devisuci windariyah; A Bagus Wasil Hamdi (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2022)
This study aims to reflect on the implementation of the Arabic Language Curriculum at MI Al-Islamiyah Karanganyar, Paiton. In addition, to find out external and internal challenges along with solutions from the implementation of the Arabic Language Curriculum at MI Al-Islamiyah Karanganyar, Paiton because with a good curriculum, it will produce good outputs. This study uses a descriptive qualitative approach. The data collection used is techniques: interviews, observation and documentation. The data analysis technique used are reduction, presentation and verification. The researcher then used the source triangulation technique to the data validity technique. The results of this study indicate that MI Al-Islamiyah Karanganyar, Paiton uses online learning media as smartphones or laptops (delivery of educational material through unique learning videos by teachers through social media such as YouTube, Facebook, Tiktok or any social media favored by students)., and digital dictionaries. The challenge is the focus of students in learning Arabic online and students do not yet understand the importance of independent learning. The solution is that the Arabic teacher makes a video explanation accompanied by interesting animations, or other educational videos so that the material is conveyed well to students and the teacher gives students the habit of learning independently or in groups, even outside the classroom.